A Reporter in the Guise of a Tourist. The First Voyage of the "Batory" Through the Eyes of Melchior Wańkowicz - Paczkowski, Mikołaj (Porównania, 2025)
The article discusses a series of pieces written by Melchior Wańkowicz in 1936, in which the writer chronicled his participation in the maiden voyage of the transatlantic liner "Batory." These reports were originally published in the newspaper “Czas” and later compiled into the book “Anoda – Katoda” under the collective title “Pierwsza Podróż »Batorego«”." The analysis highlights the dual identity of the author as both a reporter and a tourist, emphasizing its influence on his portrayal of life aboard the ship and the destinations visited. The account written during the voyage is compared with the account found in Wańkowicz’s memoir “Tędy i owędy”, published years later. Additionally, the reminiscences of other passengers, including Arkady Fiedler, Monika Żeromska, and Izabela Stachowicz, are used as contextual material.